Warm Climate Production Guidelines for Angelonia - Richard Schoellhorn; Erin Alvarez (EDIS)
Angelonia is a popular warm-season annual that has a renewed interest for growers and consumers due to the development of several new cultivars. It is excellent for use in the landscape and in large containers, and is becoming more popular for cut flower use. Known as the summer snapdragon, this plant does best in warm climates, is drought tolerant, and really shines when snapdragons and other spring annuals begin to wither. Older varieties vary in performance. Most are treated as annuals, but in all Florida zones they can be perennial if the winter is mild. This document is ENH 877, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 15, 2002.